Formulasi Kebijakan Pengembangan Pariwisata di Provinsi Banten - Delly Maulana; Bambang Pujiyono; Rudi Subiyakto (Universitas Sultan Ageng Tirtayasa, 2023)
To increase economic growth and have an impact on society, one of which is through tourism development. Indeed, tourism in Banten Province has very good potential, both from coastal, mountain, religious, and cultural tourism. For example, Banten Province is one of the areas designated as the Tanjung Lesung Special Economic Zone. But now this area is no longer a strategic program of the Central Government. Apart from that, Banten also has religious tourism in the Old Banten area which has become a pilgrimage destination. Banten also has cultural and natural tourism, namely traditional Baduy tourism which has quite an interesting appeal for tourists who want to learn about the characteristics of the typical Baduy people. Therefore, with very good potential, it is necessary to have a comprehensive policy formulation so that this potential can develop significantly while at the same time providing maximum impact on increasing local revenue in each Regency/City in the Banten Province region and providing local community welfare. The method used in this study is a qualitative method using primary and secondary data and using data analysis techniques with the help of Atlas Ti software (looking for potential, problem identification, and policy alternatives) and Process Hierarchy Analysis (AHP) to find recommendations that are prioritized and most the best to be the solution for tourism development in Banten Province. This research will provide an overview of the potential and policy formulation for tourism development in Banten Province.